Data requirements for improving the Quantitative Risk Assessment of liquid hydrogen storage systems - Correa-Jullian, Camila; Groth, Katrina M. (International journal of hydrogen energy, 2022)
Quantitative Risk Assessment (QRA) supports the development of risk-informed safety codes and standards which are employed to enable the safe deployment of hydrogen technologies essential to decarbonize the transportation sector. System reliability data is a necessary input for rigorous QRA. The lack of reliability data for bulk liquid hydrogen (LH2) storage systems located on site at fueling stations limits the use of QRAs. In turn, this hinders the ability to develop the necessary safety codes and standards that enable worldwide deployment of these stations. Through a QRA-based analysis of a LH2 storage system, this work focuses on identifying relevant scenario and probability data currently available and ascertaining future data collection requirements regarding risks specific to liquid hydrogen releases. The work developed consists of the analysis of a general bulk LH2 storage system design located at a hydrogen fueling station. Failure Mode and Effect Analysis (FMEA) and traditional QRA modeling tools such as Event Sequence Diagrams (ESD) and Fault Tree Analysis (FTA) are employed to identify, rank, and model risk scenarios related to the release of LH2. Based on this analysis, scenario and reliability data needs to add LH2-related components to QRA are identified with the purpose of improving the future safety and risk assessment of these systems. •Employed FMEA to identify failure scenarios for an on-site LH2 storage system.•Developed Event Sequence Diagram models of Liquid Hydrogen release scenarios.•Assessed LH2 storage system reliability with Fault Tree Analysis and generic data.•Identified data needs to add LH2 scenarios and components to QRA.